PENGEMBANGAN BAHAN AJAR FIKSI MEMBACA INTENSIF CERITA PETUALANGAN BERBASIS EKOLOGI SISWA SEKOLAH DASAR - Noer Intan Novitasari; Azamul Fadhly Noor Muhammad (Universitas Kanjuruhan Malang, 2020)
AbstractThe aims of this study is create intensive reading material adventure stories based ecology on 5th grade elementary school students. The specific purposes of this study are to produce ecology-based teaching material that can develop students' reading skills and describe the validity of ecology-based intensive reading material. This type of development research is an ADDIE experimental model. The data analysis technique consisted of qualitative and quantitative descriptive analysis techniques. The questionnaire result data in the form of score analysis uses a rating scale, while the results of the assessment of teaching materials from the validator use a percentage (%). The subjects of this study were selected from the fifth grade students of the Diponegoro Cluster of Majenang District in the 2018/2019 academic year as many as 102 students. The research sample of 15 students from three different schools. The results of this study indicate that intensive reading teaching material based on ecology based on effective and valid adventure stories is used in intensive reading learning in class V of SDN throughout the Diponegoro Cluster, Majenang District Abstrak Tujuan penelitian ini adalah menghasilkan bahan ajar membaca intensif cerita petualangan berbasis ekologi bagi siswa kelas 5 sekolah dasar. Adapun tujuan khusus dalam penelitian ini, yakni (1) menghasilkan produk bahan ajar berbasis ekologi yang dapat mengembangkan kemampuan membaca intensif siswa dan (2) mendeskripsikan kevalidan bahan ajar membaca intensif cerita petualangan berbasis ekologi. Jenis penelitian pengembangan ini mengadopsi model ADDIE. Teknik analisis data terdiri dari teknik analisis deskriptif kualitatif dan kuantitatif. Data hasil angket dalam bentuk analisis skor menggunakan rating scale, sedangkan hasil penilaian bahan ajar dari validator menggunakan persentase (%). Subjek penelitian ini dipilih dari siswa kelas V SD se-Gugus Diponegoro Kecamatan Majenang tahun pelajaran 2018/2019 sebanyak 102 siswa. Sampel penelitian 15 siswa dari tiga sekolah yang berbeda. Hasil dari penelitian ini menunjukkan bahwa bahan ajar membaca intensif materi cerita petualangan berbasis ekologi efektif dan valid digunakan pada pembelajaran membaca intensif di kelas V SDN se Gugus Diponegoro Kecamatan Majenang.